Photostabilization of ketoprofen by inclusion in glycyrrhizin micelles and gel nanoparticles. (7th September 2022) - Selyutina, Olga Yu.; Babenko, Simon V.; Kruppa, Alexander I.; Leshina, Tatyana V.; Polyakov, Nikolay E.
Abstract : Ketoprofen (KP) solubilization in glycyrrhizin micelle and gel nanoparticle aqueous solutions prevents photodegradation under UV irradiation. Abstract : Ketoprofen (KP) is known to be the most photosensitive among the nonsteroidal anti-inflammatory drugs and may induce phototoxic and photoallergic reactions. Phototoxic side effects of KP are associated with the formation of active free radicals under sunlight irradiation. The application of non-covalent supramolecular complexes of photosensitive drugs with appropriate carriers in some cases allows overcoming this problem and significantly enhancing the drug photostability. In this article we attempt to use glycyrrhizin (GA) – the active component of licorice root which exhibits own anti-inflammatory activity and is widely used as a drug delivery vehicle, since the ability of GA to form inclusion complexes, micelles and gels is well known. Thus, the drug solubilization into the micelles and gel nanoparticles of GA was used to increase KP photostability. The main source of KP toxicity, the benzyl, ketyl, CO2 H free radicals and solvated electrons, was identified earlier and confirmed in this study using the chemically induced dynamic nuclear polarization (CIDNP) technique. CIDNP and NMR techniques also have been applied in this work to study the peculiarities of ketoprofen photolysis in the inclusion complexes. It was shown that the presence of GA significantly affects the bulk processes due to the trapping of the abovementioned short-lived paramagnetic particles by glycyrrhizin. Besides, it was found that incorporation of ketoprofen into micelles or gel nanoparticles significantly decreases its photodegradation rate. In general, the obtained results might be useful in the design of ketoprofen formulations for topical application.